Cu/Fe3O4 catalyst for water gas shift reaction: Insight into the effect of Fe2+ and Fe3+ distribution in Fe3O4. (18th March 2020) - Chen, Chongqi; Ren, Hongju; Zhou, Jianke; Luo, Yu; Zhan, Yingying; Au, Chaktong; Lin, Xingyi; Jiang, Lilong
Abstract: Two precursors, namely, p -CFO- T (tetragonal) and p -CFO- C (cubic), were fabricated by a sol-gel method via citric acid and poly(vinyl alcohol) complexation, respectively. After H2 -reduction, the two were converted to Cu/Fe3 O4 catalysts of different complexions, which are named as CFO-CA and CFO-PVA, respectively. The distribution of Fe 2+ and Fe 3+ in the Cu/Fe3 O4 catalysts was studied by Raman and XPS techniques. It was disclosed that the distribution of Fe 2+ and Fe 3+ in Fe3 O4 has an effect on Cu–Fe3 O4 interaction and catalyst surface basicity. Compared to CFO-PVA, CFO-CA has a larger amount of Fe 3+, which mostly sits at the octahedral sites, leading to stronger Cu–Fe3 O4 interaction, and a larger amount of catalyst surface sites that are of weak basicity. As a result, the critical elementary steps of WGS reaction, viz. water dissociation, –COOH decomposition and CO2 desorption are promoted as reflected in the lower E a and higher catalytic activity of CFO-CA. Graphical abstract: Image 1 Highlights: Tetragonal and cubic CuFe2 O4 precursors were fabricated by a sol-gel method. Reducing the two CuFe2 O4 precursors led to distinct cations distribution in Fe3 O4 . Strength of Cu–Fe3 O4 interaction and catalyst surface basicity are manipulated. CuFe2 O4 - T is an excellent precursor for Cu/Fe3 O4 catalyst efficient in WGS reaction.